Comportamento de duas cultivares de crisântemo de jardim (Dendranthema indicum), produzidas em vasos - Rodrigues, Marcelo Antonio de Souza (2005)
The species Dendranthema indicum, a type of garden chrysanthemum, has the following characteristics: perennial, low height, rustic, and produces a great amount of inflorescences. The commercial production of this species in vase is done in a na empirically way. The objective of this study was to determine the cultivar cycle, size of vase, number of cuttings, environment adaptability, the topiary technique and qualitative standards of commercialization for two cultivars, Papiro and Veria Dark. The experiment was performed in three different sizes of vases (numbers 11, 15 and 20), using only one plant per vase, which received 4, 6 and 7 cuttings, respectively. Increasing the vase size increased the plant size, and the number of inflorescences but reduced the diameter of these. The environment conditions at Santa Maria, RS, are not limitating to production of vases with plants with topiary technique. However, the cycle of cultivar Veria Dark was increased in one week. It is possible to obtain plants with good quality cultivating them in vases number 15 or 20, with a minimum of five cuttings number. It was not possible to obtain plants of cultivar Veria Dark, with quality for commercialization using vase 11. The ratio of height of plant/height of vase and closing were the parameters that better evaluated the quality of the vases